Sprifermin: a recombinant human fibroblast growth factor 18 for the treatment of knee osteoarthritis. (2nd September 2021) - Li, Jia; Wang, Xiaoshuai; Ruan, Guangfeng; Zhu, Zhaohua; Ding, Changhai
ABSTRACT: Introduction: Osteoarthritis (OA) is a serious and incurable disease leading the disability. Surgical treatment is the last but not necessarily the best approach for patients with high risks and costs. However, there are no disease-modifying OA drugs (DMOADs) developed for the disease so far, leaving a huge unmet need for drug treatments. Sprifermin is a recombinant human fibroblast growth factor 18 (rhFGF18) and has been confirmed to have anabolic effects on articular cartilage, which makes it a promising DMOAD. Areas covered: The content of this review includes overview of the market, discovery and development, molecular mechanism, preclinical studies, clinical efficacy, safety, and tolerability of sprifermin. It examines the potential of sprifermin as a disease modifying drug for the treatment of knee OA. Expert opinion: Sprifermin could be one of the most promising DMOADs, especially for cartilage phenotype. Current studies show good tolerability and no safety concerns. Well-designed phase 3 clinical trials are required to examine its effects on symptoms and cartilage loss in knee OA.